Driving Forces Shaping Gig Economy Perceptions in Mongolia: A Multifactorial PLS-SEM Approach - Batmunkh, Altanshagai; Lakner, Zoltan (Emerging Science Journal, 2025)
The gig economy, characterized by flexible, task-based, and technology-driven work, has become an increasingly important aspect of modern labor markets, especially in emerging economies. This study aims to assess the perceptions of the gig economy in Mongolia by examining the influence of five main factors: economic, social, technological, personal, and work-environmental. Using the Partial Least Squares Structural Equation Modelling (PLS-SEM) framework, data were collected through a structured questionnaire (Likert Scale) distributed to 43 participants in Mongolia. The results revealed mixed findings across the hypothesized relationships. Economic factors significantly influenced perceptions of the gig economy (H1: β = 0.207, p = 0.014), but their impact on the gig work environment was not supported (H1a: β = 0.339, p = 0.069). Social factors did not significantly influence gig economy perceptions (H2: β = 0.254, p = 0.111), but they had a positive impact on the gig work environment (H2a: β = 0.431, p = 0.023). Technological factors positively influenced gig economy perceptions (H3: β = 0.035, p = 0.042). However, personal factors did not have a significant impact (H4: β = 0.251, p = 0.116). Finally, the gig work environment positively influenced perceptions of the gig economy (H5: β = 0.247, p = 0.008). These findings highlight the multifaceted and complex nature of gig economy perceptions in Mongolia, highlighting the importance of economic and technological factors as well as the role of the work environment in shaping overall perceptions. This study contributes to a deeper understanding of the driving forces behind gig economy perceptions in emerging economies such as Mongolia.